1979
DOI: 10.1007/bf01968288
|View full text |Cite
|
Sign up to set email alerts
|

Plasma steroid and protein hormone concentrations in patients with benign prostatic hypertrophy and in normal men

Abstract: Serum levels of testosterone, FSH, LH and prolactin were measured by RIA in patients with BPH (benign prostatic hypertrophy) and in control men. The testosterone concentrations in the BPH group were significantly lower than that of the control group. Serum concentrations of FSH, LH, prolactin and estradiol, did not differ significantly in the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…It is supported by previous evidence of reduced plasma T levels and elevated plasma estradiol (E2) levels in patients with BPH [30], [31] and of a higher E2/T ratio in aging men at greater risk of prostate disease [28]. However, the variation in serum concentrations of E2 may not accurately reflect intraprostatic levels, because E2 is produced from T by the enzyme aromatase (CYP19A1, EC1.14.14.1), which interestingly is increased in the malignant human prostate [32].…”
Section: Introductionsupporting
confidence: 68%
“…It is supported by previous evidence of reduced plasma T levels and elevated plasma estradiol (E2) levels in patients with BPH [30], [31] and of a higher E2/T ratio in aging men at greater risk of prostate disease [28]. However, the variation in serum concentrations of E2 may not accurately reflect intraprostatic levels, because E2 is produced from T by the enzyme aromatase (CYP19A1, EC1.14.14.1), which interestingly is increased in the malignant human prostate [32].…”
Section: Introductionsupporting
confidence: 68%
“…Regarding the plasma levels of other hormones, while testosterone levels show a significant decrease in BPH patients, no significant alteration could be shown with respect to FSH, LH, prolactin and estradiol levels [10]. While it has been reported that serum LH, FSH and progesterone levels have been found to be more elevated in patients with BPH than the control cases [11], in their original study Sasagawa et al [7] have been able to show that plasma prolactin levels are elevated more significant- 5.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the changes of plasma estrogen concentration in BPH patients remain controversial. Drafta et a1 [ 121 found a decrease of plasma estrone and estradiol levels in BPH patients, whereas several authors [2,13,14] have demonstrated no significant effect on estrogen. The present study was undertaken to demonstrate any difference in circulating unconjugated and glucuronide derivatives of progestins, androgens, and estrogens between patients with BPH and age matched controls.…”
Section: Introductionmentioning
confidence: 99%